Combining Vγ9Vδ2 T Cells with a Lipophilic Bisphosphonate Efficiently Kills Activated Hepatic Stellate Cells - Zhou, Xiaoying; Gu, Yanzheng; Xiao, Hongying; Kang, Ning; Xie, Yonghua; Zhang, Guangbo; Shi, Yan; Hu, Xiaoyu; Oldfield, Eric; Zhang, Xueguang; Zhang, Yonghui (Frontiers in Immunology, 2017)
Activated hepatic stellate cells (aHSC) are now established as a central driver of fibrosis in human liver injury. In the presence of chronic or repeated injury, fibrosis, cirrhosis and hepatocellular carcinoma (HCC) can occur, so there is interest in down-regulating aHSC activity in order to treat these diseases. Here, we report that Vγ9Vδ2 T cells are reduced in patients with liver cirrhosis, stimulating us to investigate possible interactions between Vγ9Vδ2 T cells and aHSC. We find that Vγ9Vδ2 T cells kill aHSC and killing is enhanced when aHSC are pre-treated with BPH-1236, a lipophilic analog of the bone resorption drug zoledronate. Cytotoxicity is mediated by direct cell-to-cell contact as shown by Transwell experiments and atomic force microscopy, with BPH-1236 increasing the adhesion between aHSC and Vγ9Vδ2 T cells. Mechanistically, BPH-1236 functions by inhibiting farnesyl diphosphate synthase, leading to accumulation of the phosphoantigen isopentenyl diphosphate and recognition by Vγ9Vδ2 T cells. The cytolytic process is largely dependent on the perforin/granzyme B pathway. In a Rag2-/-γc-/- immune-deficient mouse model, we find that Vγ9Vδ2 T cells home-in to the liver, and when accompanied by BPH-1236, kill not only orthotopic aHSC but also orthotopic HCC tumors. Collectively, our results provide the first proof-of-concept of a novel immunotherapeutic strategy for the treatment of fibrosis-cirrhosis-hepatocellular carcinoma (HCC) diseases using adoptively transferred Vγ9Vδ2 T cells, combined with a lipophilic bisphosphonate.